3-D N-doped porous graphene-like network and vanadium nitride co-promoted Pt electrocatalyst with high activity and stability for the oxygen reduction reaction. Issue 114 (3rd November 2015) - Li, Zesheng; Li, Bolin; Liu, Zhisen; Liu, Zhenghui; Li, Dehao
Abstract : Novel ternary 3DNPG/VN/Pt hybrid architectures with unique 3D network configuration and very high activity are presented for ORR. Abstract : A three dimensional (3D) N-doped porous graphene and vanadium nitride co-promoted Pt (3DNPG/VN/Pt) electrocatalyst was first presented in this work. Such multi-component catalysts exhibited superior performance for the oxygen reduction reaction (ORR). The mass activity of 3DNPG/VN/Pt is 535 mA mg −1 Pt (after IR correction), which is 4.35 times as high as that of commercial Pt/C (123 mA mg −1 Pt). Higher stability of 3DNPG/VN/Pt is also demonstrated in comparison with the commercial Pt/C.